2003
DOI: 10.1002/cyto.a.10010
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying cell scattering: The blob algorithm revisited

Abstract: Background: A method to objectively quantify cell scattering would permit quantitative evaluation of therapies and compounds intended to affect this physiologic process, which has relevance to normal (e.g., development) and pathologic (e.g., metastasis) events. Methods: A grid-based modified blob analysis was performed on a set of images of Madin-Darby Canine Kidney (MDCK) cells to quantify the following parameters: the number of cellular clusters in each image, the size of the clusters in terms of pixel count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Small staining artifacts (mainly resulting from nonstaining endothelial nuclei) were removed by applying a two-pixel opening function. Vessels within the binary mask were identified using connected component analysis (22). Several variables for each connected component within the binary mask were then calculated:…”
Section: Methodsmentioning
confidence: 99%
“…Small staining artifacts (mainly resulting from nonstaining endothelial nuclei) were removed by applying a two-pixel opening function. Vessels within the binary mask were identified using connected component analysis (22). Several variables for each connected component within the binary mask were then calculated:…”
Section: Methodsmentioning
confidence: 99%
“…1A, b). Quantitative analysis of the scattering produced by the addition of plasminogen was performed using a modified Blob algorithm [16] based on numerical quantification of cell clusters (see Materials and methods). The method identifies non-scattered cells as single clusters, whereas scattered cells present as numerous clusters.…”
Section: Resultsmentioning
confidence: 99%
“…Images were downsampled 50% and then automatically thresholded as described elsewhere [16]. Since DIC imaging emphasizes edges, the resulting binary mask required processing to fully capture the cellular regions.…”
Section: Quantification Of Cell Scatteringmentioning
confidence: 99%
“…Only few attempts have been made to quantify objective measures for cell scattering. Kort et al [24] suggested a simple image-processing application that detects and counts clusters of cells and single cells based on fluorescent marking. Although proving high correlation with manual counting, they do not show a quantitative measure to describe cell scattering.…”
Section: Introductionmentioning
confidence: 99%